O socjolekcie współczesnej młodzieży słów kilka (Conversatoria Linguistica, 2018)
The language spoken on a daily basis by different social groups not only allows us to explore their specificity, but also reflects the values they cultivate or lack. Youth intellect gives a picture of young people's attitude towards the surrounding world, their perception and interpretation. The dynamism of changes taking place in it, thanks to numerous abbreviations, neologisms, borrowings and metamorphoses, reveals the relations between the young generation and reality. It emphasizes the individuality of this social group, whose language is characterized by numerous emotionalisms and creations and dynamic exchange of language units.